IMPLEMENTASI SISTEM PENJAMINAN MUTU MADRASAH - Muaripin, Muaripin; Nugraha, Firman; Prawira, Yudha Andana (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The purpose of this study was to analyze the implementation of the Education Quality Assurance System (SPMP) based on Integrated Quality Management at MTs Negeri West Bandung Regency in terms of program planning, program implementation, program monitoring and evaluation, obstacles and efforts to overcome obstacles in implementing SPMP and the success rate of SPMP in improving quality of education. This study uses a qualitative approach with analytical descriptive method. The object of the research is the head of the madrasa, madrasa teacher, TU, committee chairman, supervisor, and students. Data collection techniques were carried out by observation, interviews, documentation and literature study. The analysis and interpretation technique are carried out by data reduction, data display, triangulation, conclusion drawing and data verification. The results showed that the optimal implementation of SPMP based on Integrated Quality Management in MTs Negeri West Bandung Regency was able to improve the quality of madrasas. This can be seen from the activities of planning programs, implementing programs, carrying out monitoring and evaluation, efforts to overcome obstacles in the implementation of SPMP and the success rate of SPMP in improving the quality of madrasas, so that madrasas are able to achieve SNP and are able to develop sustainable quality madrasas.Keywords: Quality Management; Madrasah Quality; Quality Assurance System